2011
DOI: 10.1002/cne.22657
|View full text |Cite
|
Sign up to set email alerts
|

Cytoarchitecture and ultrastructure of neural stem cell niches and neurogenic complexes maintaining adult neurogenesis in the olfactory midbrain of spiny lobsters, Panulirus argus

Abstract: New interneurons are continuously generated in small proliferation zones within neuronal somata clusters in the olfactory deutocerebrum of adult decapod crustaceans. Each proliferation zone is connected to a clump of cells containing one neural stem cell (i.e., adult neuroblast), thus forming a “neurogenic complex.” Here we provide a detailed analysis of the cytoarchitecture of neurogenic complexes in adult spiny lobsters, Panulirus argus, based on transmission electron microscopy and labeling with cell-type-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 124 publications
(221 reference statements)
2
30
1
Order By: Relevance
“…The manufacturer tested the specificity of this antibody by western blot and found that it recognized a single band of 17KDa in colchemid-arrested HeLa cells as predicted. This antibody has been reported to detect mitotic cells in several species, including the optic tectum of chick, fish, and xenopus where staining is concentrated in mitotically active nuclei that line the ventricular layer of the tectum, similar to the expression we report (Schmidt and Derby, 2011; Tibber et al, 2006; Wirsching et al, 2012). We found that the antibody labels select nuclei in the Xenopus tadpole tectal proliferative zone that display morphological features of nuclei in various phases of mitosis.…”
Section: Methodssupporting
confidence: 84%
See 1 more Smart Citation
“…The manufacturer tested the specificity of this antibody by western blot and found that it recognized a single band of 17KDa in colchemid-arrested HeLa cells as predicted. This antibody has been reported to detect mitotic cells in several species, including the optic tectum of chick, fish, and xenopus where staining is concentrated in mitotically active nuclei that line the ventricular layer of the tectum, similar to the expression we report (Schmidt and Derby, 2011; Tibber et al, 2006; Wirsching et al, 2012). We found that the antibody labels select nuclei in the Xenopus tadpole tectal proliferative zone that display morphological features of nuclei in various phases of mitosis.…”
Section: Methodssupporting
confidence: 84%
“…This antibody was raised against 5-iodo-2′-deoxyuridine conjugated to ovalbumin and binds to 5-bromo-2′-deoxyuridine as well as 5-iodo-2′-deoxyuridine, according to the manufacturer's information. Several studies have shown that this antibody specifically labels nuclei that have incorporated BrdU or IdU into their newly synthesized DNA during the S-phase of the cell cycle (Schmidt and Derby, 2011). We have previously shown that this antibody labels cells in the proliferative layer of the Xenopus optic tectum in animals that have been exposed to BrdU or IdU, and that no labeling is present in the brains of animals that have not been exposed to BrdU or IdU (Sharma and Cline, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…We proposed, therefore, that (1) primary neuronal precursor cells in the crayfish niche are not self‐renewing, and (2) a source extrinsic to the niche provides cells that replenish the niche precursor pool (Beltz et al, 2011; Benton et al, 2011). This proposal is in contrast to the view that large mitotic cells in the crayfish niche (putative neuroblasts) persist beyond embryonic life, providing a self‐renewing source of neurons (Song et al, 2009; Schmidt and Derby, 2011). To resolve this issue, we directly tested the self‐renewal capacity of niche precursor cells.…”
Section: Introductionmentioning
confidence: 72%
“…Comparably, in insects, cell proliferation takes place in mushroom bodies, as a center of multimodal integration, where newborn cells migrate into the depth of the cortex placing among the older interneurons (Cayre et al., , ). In crustaceans, adult neurogenesis is detectable in the central olfactory pathway where an overall increase in olfactory sensory neurons is evident (Schmidt and Harzsch, ; Schmidt and Derby, ). Among mammals, the cell proliferation affects the olfactory bulb, first processing stage of olfactory information, in which immature neuroblasts differentiate into two types of interneurons that integrate themselves in existent circuits (Petreanu and Alvarez‐Buylla, ; Nissant et al., ; Breton‐Provencher and Saghatelyan, ).…”
Section: Discussionmentioning
confidence: 99%
“…This fascinating process, in adult organisms, recapitulates the whole neural development from neural progenitor to fate determination passing through differentiation, migration, axonal, and dendritic development of newborn neurons, as well as synapses formation and functional integration into the existing neural circuitries (Duan et al., ; Sun et al., ). All these processes occur in animals with a complex nervous system that exhibit a range of sophisticated behaviors such as mammals (Kempermann et al., ; Gage et al., ; Gould et al., ; Amrein et al., ; Lepousez et al., ), humans included (Eriksson et al., ; Bergmann et al., ), nonmammals vertebrates (Alvarez‐Buylla et al., ; Marchioro et al., ; Zupanc et al., ; Kaslin et al., ; Simmons et al., ), and insects and crustaceans (Cayre et al., ; Dufour and Gadenne, ; Schmidt and Derby, ; Fernández‐Hernández et al., ; Benton et al., ; Kim et al., ). Mammals and invertebrates show that their adult neurogenesis is not widespread throughout the brain, but it is restricted to specific neural areas, that is, the multimodal associative centers considered the anatomical and functional substrate of the higher cognitive capabilities (Kempermann, ).…”
mentioning
confidence: 99%